A new constitutive model for recycled aggregate concrete cylinders actively confined with post-tensioned metal straps - Ram Prasad Neupane; Thanongsak Imjai; Reyes Garcia; U. Johnson Alengaram (Sustainable Structures)
The compressive strength of cylindrical columns of recycled aggregate concrete (RAC) is lower than that of equivalent normal concrete columns. Active confinement can recover some of such lower compressive strength, but limited research has examined the stress-strain behaviour of RAC cylinders with active confinement. This study proposes a new constitutive model for RAC cylinders actively confined with post-tensioned metal straps (PTMS). Using pneumatic tools, the PTMS technique involves applying a post-tensioning force to high-strength metal straps. RAC cylinders (⌀150×300 mm) with different confinement ratios (ρv = 0, 0.35, 0.52, 0.80 or 1.6) were subjected to axial compression tests to determine their maximum strength and axial strains. The RAC was produced using recycled concrete aggregate (RCA) as coarse aggregate, considering three compressive strengths: 15, 21 and 24 MPa. The test results indicate significant increases in strength and axial strains as the confinement ratio increased, with the strength increasing by 29% to 196%, and peak axial strains by 90% to 158% for ρv values of 0.35 and 1.6, respectively. Based on the test results and a regression analysis, a new stress-strain constitutive model is proposed to assess the effectiveness of the PTMS confinement on RAC. The results of this study promote the use of RAC in construction by demonstrating that the mechanical properties of RAC structural members can be effectively enhanced through the PTMS technique.